PENGARUH ARUS KAS OPERASI DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rawung, Fita Enjelina; Alexander, Stanly W.; Kalalo, Meily Y.B. (Universitas Sam Ratulangi, 2017)
Indonesian is a country that embraces the financial system on the bank. The purpose of banking is to support the implementation of national development to improve equity, economic growth, and national stability towards the improvement of people’s welfare. The purpose of this study is to determine the effect of operating cash flow and returnon asset (ROA) to stock price studies on banking companies listed on the stock exchange Indonesia. Population of 42 bank and samples used by 30 banks. In the examinations examined in this study, only the results obtained flow of operations and return on asset (ROA) that positive number and sample data overall stock price are all used because there is nonegative number. Research method used in this research is quantitative research with multiple linear regression analysis technique by using SPSS 20 program. The results showed that operating cash flow has no significant effect on stock price and return on asset (ROA) significant effect on stock price. As a recommendation, investors ahould be able to pay attention and analyze operating cash flow and return on asset (ROA) and stock price movements to gain profit.Keywords : Operating Cash Flow, Retur On Asset (ROA) and Stock Price